Implementasi Strategi Pembelajaran Langsung Dalam Meningkatkan Prestasi Siswa SMP Pertiwi 2 Padang Dalam Pembelajaran Pendidikan Agama Islam - Aisyah Qurotul Sabila; Elvira Darmawanti; Ulfa Aulia; Gusmaneli Gusmaneli (STIKes Ibnu Sina Ajibarang, 2024)
Direct learning strategy is a learning approach that involves the teacher as the main source of knowledge who provides information directly to students. In this strategy, teachers use various techniques such as lectures, demonstrations, and discussions to convey lesson material to students. Research has shown that hands-on learning strategies are effective in improving students' understanding of course material, increasing student engagement, and facilitating the transfer of knowledge to real-world situations. However, there is also criticism of this strategy because it lacks space for students to actively participate in learning. Therefore, teachers need to consider using direct learning strategies wisely and integrating active learning elements to increase learning effectiveness.